2021
DOI: 10.1259/bjrcr.20210025
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal catheter plasty. An alternative technique to remove tethered abdominal surgical drains

Abstract: Objective: Retained surgical drains can lead to significant complications including gastrointestinal fistulae, abscess formation and intestinal obstruction. Today, there is little in the literature describing the role of Interventional Radiology (IR) in assisting the removal of surgical drains. We describe the use of the well-established intraluminal catheter plasty technique, previously used for the removal of adhered central venous catheters, in order to remove a tethered abdominal drain. Methods and materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…1 In searching for strategies that may make a dent on this dismal mortality rate, investigators have, in the last decade, shown renewed interest in the potential beneficial role of venoarterial (V-A) extracorporeal membrane oxygenation (ECMO) in the treatment of patients with high-risk PE and, in particular, those with circulatory collapse or cardiac arrest. 2 3 4 5 6 7 8 9 10 11…”
mentioning
confidence: 99%
“…1 In searching for strategies that may make a dent on this dismal mortality rate, investigators have, in the last decade, shown renewed interest in the potential beneficial role of venoarterial (V-A) extracorporeal membrane oxygenation (ECMO) in the treatment of patients with high-risk PE and, in particular, those with circulatory collapse or cardiac arrest. 2 3 4 5 6 7 8 9 10 11…”
mentioning
confidence: 99%